Laporan kasus: demam rematik akut pada anak - Fitriana Melinda; Anak Agung Made Sucipta (DiscoverSys Inc., 2021)
Background: Acute rheumatic fever is an autoimmune sequelae caused by group A streptococcal infection. Acute rheumatic fever causes a systemic inflammatory response followed by disorders of the brain, heart, skin, and joints. This disease tends to recur and begins with Streptococcus beta-hemolytic group A infection in the respiratory tract.Case description: A boy aged 9 years 7 months with complaints of pain in both legs so that his legs are difficult to move since one day before being admitted to the hospital. The patient also had a fever for about 1 week, cough and sore throat before complaining of joint pain but the patient did not seek treatment. The patient had a history of recurrent sore throat and was rarely treated. Physical examination revealed that both knees were erythematous, warm and there was tenderness and limited leg movement due to pain. On examination of the tonsils found T2-T2 is not hyperemic. Laboratory examination showed positive ASTO. The diagnosis was made as acute rheumatic fever and treated with erythromycin and aspirin.Conclusion: Acute rheumatic fever can be established using the Jones criteria and modified WHO. In patients with typical symptoms or manifestations according to the major and minor criteria, it will be easier to establish the diagnosis. Latar belakang: Demam rematik akut adalah suatu sekuele autoimun akibat infeksi streptokokus grup A. Kondisi demam rematik akut menyebabkan suatu respon inflamasi sistemik yang diikuti oleh adanya gangguan pada organ otak, jantung, kulit, dan sendi. Penyakit ini cenderung terjadi berulang dan diawali dengan infeksi Streptococcus beta hemolyticus grup A pada saluran napas.Deskripsi kasus: Anak laki-laki berusia 9 tahun 7 bulan dengan keluhan nyeri pada kedua kaki sehingga kaki sulit untuk digerakkan sejak satu hari sebelum masuk RS. Pasien juga mengalami demam sekitar 1 minggu, batuk dan nyeri tenggorok sebelum mengalami keluhan nyeri sendi namun pasien tidak berobat. Pasien memiliki riwayat nyeri tenggorok berulang dan jarang diobati. Pemeriksaan fisik didapatkan kedua lutut eritema, teraba hangat dan terdapat nyeri tekan serta gerakan kaki terbatas karena nyeri. Pada pemeriksaan tonsil didapatkan T2-T2 tidak hiperemis. Pemeriksaan laboratorium menunjukkan ASTO positif. Diagnosis ditegakkan sebagai demam reumatik akut dan diberikan terapi eritromisin dan aspirin.Simpulan: Demam rematik akut dapat ditegakkan menggunakan kriteria Jones dan modifikasi WHO. Pada pasien dengan gejala khas atau manifestasi sesuai dengan kriteria mayor dan minor akan mempermudah penegakkan diagnosis.